Direct and Indirect Determinants of Obesity: The Case of Indonesia - Cornelia Römling; Matin Qaim (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Overweight and obesity are becoming serious issues in many developing countries. Since undernutrition is not completely eradicated yet, these countries face a dual burden that obstructs economic development. We analyze the nutrition transition in Indonesia using longitudinal data from the Indonesian Family and Life Survey, covering the period between 1993 and 2007. Obesity has been increasing remarkably across all population groups, including rural and low income strata. Prevalence rates are particularly high for women. We also develop a framework to analyze direct and indirect determinants of body mass index. This differentiation has rarely been made in previous research, but appears useful for policy making purposes. Regression models show that changing food consumption patterns coupled with decreasing physical activity levels during work and leisure time directly contribute to increasing obesity. Education, income, and marital status are significant determinants that influence nutritional status more indirectly. Change regressions underline that there are important path-dependencies. From a policy perspective, nutrition awareness and education campaigns, combined with programs to support leisure time exercise, seem to be most promising to contain the obesity pandemic. Women should be at the center of policy attention.
Additional information: This paper also appears as no. 4 in the "GlobalFood Discussion Papers Series" from RTG 1666 GlobalFood Transformation of Global Agri-Food Systems: "Trends, Driving Forces, and Implications for Developing Countries", Georg-August-University of Göttingen
Keywords: I10; O12; 330; Obesity; Overweight; Nutrition Transition; Asia; Indonesia